Potential of colonoscopy as a treatment for intussusception in children - Edmar Tafner; Philipe Tafner; Cornelius Mittledorf; Jose Pinhata; Ana Luisa Silva; Simone Pilli; José Guilherme da Silva; Renato T. Hassegawa; Luis Maruta; Celso Christiano; Lincoln Andrada (Endoscopy International Open, 2017)
Background and study aims Invagination, which can occur in any part of the intestine, usually affects children and is the second most common cause of intestinal obstruction after pyloric stenosis. The cause of these intussusceptions in children is usually unknown and they typically occur within the ileocolic region. Management of pediatric patients with the condition often consists of surgical intervention. However, this retrospective study from the University Hospital of the University of São Paulo, Brazil, reports a series of cases of intussusception in children in whom a colonoscopy was used to reverse the intussusception. Patients and methods From April 2010 to January 2015, 30 pediatric patients underwent a colonoscopy as an noninvasive method for treatment of children’s intestinal intussusception. Results Overall, treatment with colonoscopy was successful in reversing invagination in 66.7 % of the patients. However, 33.3 % of patients required surgery to resolve the intussusception. Conclusion Noninvasive colonoscopy is a potential treatment for intussusception in children.